2017
DOI: 10.1097/rct.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heart Rate on Exposure Window and Best Phase for Stress Perfusion Computed Tomography

Abstract: Stress myocardial CTP imaging can be performed using prospective electrocardiography triggering, an exposure window of 75% to 95%, and β-blockade resulting in good or excellent image quality in the majority (80%) of patients while maintaining a low effective radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The administration of beta-blockers before a CCTA examination improves interpretability, which is mediated via the effect of lowering the heart rate and thereby decreasing cardiac motion. 27 In addition, beta-blocker therapy does not seem to affect the ability of myocardial perfusion imaging to identify ischemia. 28,29 However, if stress perfusion is performed as a stand-alone examination, administration of beta-blockers before the acquisition is not recommended.…”
Section: Beta-blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of beta-blockers before a CCTA examination improves interpretability, which is mediated via the effect of lowering the heart rate and thereby decreasing cardiac motion. 27 In addition, beta-blocker therapy does not seem to affect the ability of myocardial perfusion imaging to identify ischemia. 28,29 However, if stress perfusion is performed as a stand-alone examination, administration of beta-blockers before the acquisition is not recommended.…”
Section: Beta-blockersmentioning
confidence: 99%
“…A critical issue in cardiac CT imaging is motion. Using retrospectively gated static perfusion, it was found that the best motion-free images were noted in mid-to-end diastole in 79% of cases and that the best phase occurs later in the R-R cycle as the heart rate increases 27…”
Section: Ct Perfusion For Detection Of Myocardial Ischemiamentioning
confidence: 99%